2014
DOI: 10.1038/modpathol.2013.219
|View full text |Cite
|
Sign up to set email alerts
|

Lack of presence of the human cytomegalovirus in human glioblastoma

Abstract: Recent reports have indicated human cytomegalovirus (HCMV) to be associated with human glioblastoma carcinogenesis. In established examples of viral carcinogenesis, viral DNA and one or more of its products have been detected in most tumor cells of biopsies in the majority of cases. To test whether HCMV is associated with human glioblastoma based on this criterion, we measured the number of viral DNA molecules per cell in both frozen and paraffin-embedded tumor biopsies from 58 patients using real-time quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 31 publications
1
48
0
1
Order By: Relevance
“…Interestingly, the authors noted that the HCMV positivity demonstrated in a few samples were actually the HCMV antibodies binding to non-viral human proteins such as human albumin and myelin basic protein. [34] This finding suggests a previously unknown cross-reactivity among HCMV antibodies. Another study by Holdhoff et al [35] assessed whether altering experimental conditions could generate false positive results.…”
Section: Authors Number Of Samples Analyzed Detection Methods Analytementioning
confidence: 61%
See 2 more Smart Citations
“…Interestingly, the authors noted that the HCMV positivity demonstrated in a few samples were actually the HCMV antibodies binding to non-viral human proteins such as human albumin and myelin basic protein. [34] This finding suggests a previously unknown cross-reactivity among HCMV antibodies. Another study by Holdhoff et al [35] assessed whether altering experimental conditions could generate false positive results.…”
Section: Authors Number Of Samples Analyzed Detection Methods Analytementioning
confidence: 61%
“…[61] A few recent studies may shed light onto why there is such discrepancy observed in the literature. A study by Yamashita et al [34] attempted to detect HCMV in GBM samples through a wide range of detection methods. They were unable to detect the presence of HCMV in many of the samples.…”
Section: Authors Number Of Samples Analyzed Detection Methods Analytementioning
confidence: 99%
See 1 more Smart Citation
“…Of our entire glioblastoma patients, 30.5% were pp65 positive in tumor, whereas 12% had CMV DNA in blood. The latter may be indicative of reactivation as a consequence of changes in the immune function of patients as CMV generally establishes latency after primary infection during childhood or adolescence (55). One difficulty is that there is currently no consensus regarding the best method for demonstrating CMV positivity in glioblastoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…For this study we used the automated method and the commercially available antibody (prediluted antibody cocktail, clone DDG9/CCH2, reacting with an immediate early antigen and an early CMV antigen, DDG9 reacts with 76 kD protein, whereas CCH2 reacts with a 43 kD protein) that the community routinely use for diagnostic purpose on formalin fixed and paraffin embedded specimens. This choice was based on the fact that the methodological changes that improve the sensibility of the immunoreactions also might potentially increase the risk of false positive as recently demonstrated [11]. On the other hand it has been suggested that the standard immunohistochemical protocols might not recognize a low viral load.…”
Section: Resultsmentioning
confidence: 99%